Polyvinylidene fluoride-polyacrylate separation membrane material as well as preparation method and application thereof
By blending PVDF and PAA, the separation of ethanol/water by using phase conversion method and low-pressure conditions for normal temperature and low pressure, the problems of high energy consumption, high cost and equipment complexity in the existing technology are solved, and high efficiency and low cost are achieved ethanol/water separation effect, and excellent mechanical properties and anti-pollution ability.
Patent Information
- Application Number
- CN202411599472.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art has problems of high energy consumption, high cost and equipment complexity in ethanol/water separation, and the mechanical properties and soil resistance of traditional separation membrane materials are insufficient, making it difficult to achieve efficient and low-voltage separation at low cost.
Polyvinylidene fluoride (PVDF) and polyacrylate (PAA) were blended with phase conversion method to prepare separation membrane materials, and the separation of ethanol/water was performed using room temperature and low pressure conditions, which simplified the preparation process and reduced energy consumption.
It realizes efficient separation of ethanol/water mixture under low pressure conditions at room temperature, the separation flux is not less than 0.8L·m-2·h-1, the cutoff rate is stable at more than 10%, and has excellent mechanical properties and Anti-pollution ability, suitable for long-term use.
Smart Images

Figure CN119425420A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of separation membrane technology, and in particular to a polyvinylidene fluoride-polyacrylic acid salt separation membrane material and a preparation method and application thereof. Background Art
[0002] As an important raw material in the fields of food, chemical industry, medical treatment and energy, ethanol has a wide range of applications and huge economic value. At present, biomass fermentation has good development prospects due to its advantages such as wide source of raw materials, low energy consumption and environmental friendliness. However, the bioethanol produced by the fermentation method is usually at a low concentration (<20vol%), so the dehydration and concentration of ethanol becomes a key link in this method and a decisive factor in production economy.
[0003] Traditional ethanol / water separation techniques such as azeotropy, distillation, extraction and adsorption all have the disadvantages of high energy consumption and high cost. Membrane separation technology has attracted more and more attention due to its high cost-effectiveness and environmental friendliness. Among them, the energy consumption of membrane distillation and pervaporation membrane methods is significantly superior to that of traditional methods. CN101259385A prepared quaternary aminated chitosan for pervaporation membrane for ethanol / water separation by phase inversion method, but such methods still inevitably introduce phase change processes such as vaporization and liquefaction and cause considerable energy consumption and complex equipment and processes. Although methods such as reverse osmosis and nanofiltration do not involve phase change, they require higher operating pressures, which leads to increased equipment costs and potential safety hazards.
[0004] The separation membrane is a key component of the pervaporation equipment, and its selectivity and mechanical properties are important guarantees for separation performance. Polyacrylate (PAS) is highly hydrophilic and has insufficient mechanical strength, so it cannot be directly formed into a membrane for separating ethanol / water. CN117138606 A uses free radical polymerization of polyacrylate to modify cellulose membrane as a low-pressure ethanol separation membrane. Specifically, PAA is introduced by initiating polymerization directly on the surface of the finished cellulose membrane. However, the preparation process is complicated, requiring simultaneous and multiple temperature adjustments and nitrogen gas introduction. In addition, more raw materials are added, and the controllability is not strong. The maximum filtration flux of the resulting separation membrane is only 0.073 mL cm -2 ·h -1 At the same time, since polyacrylate and cellulose materials are both highly polar substances with poor antifouling properties, the reproducibility and long-term utilization of the membrane are poor. Therefore, providing a membrane material suitable for separating ethanol / water at room temperature and low pressure, which has a simple preparation method, adjustable separation efficiency and flux, and can be used for a long time, has broad application prospects. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a polyvinylidene fluoride-polyacrylate separation membrane material.
[0006] Another object of the present invention is to provide a method for preparing a polyvinylidene fluoride-polyacrylate separation membrane material. The present invention uses a phase inversion method to prepare a membrane material suitable for low-pressure separation of ethanol / water at room temperature using PAS and PVDF as membrane materials, eliminating the need for heating and greatly reducing energy consumption. At the same time, the introduction of PVDF gives it a certain mechanical strength and anti-swelling and anti-pollution properties, making it suitable for long-term use.
[0007] Another object of the present invention is to provide an application of the polyvinylidene fluoride-polyacrylate separation membrane material.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A polyvinylidene fluoride-polyacrylic acid salt separation membrane material, the raw materials include polyvinylidene fluoride PVDF and polyacrylic acid PAA, and are prepared by a phase inversion method;
[0010] The mass proportion of the PAA is 20% to 40%, and the mass proportion refers to the ratio of the sum of the masses of PAA to PVDF and PAA.
[0011] Preferably, the polyvinylidene fluoride-polyacrylic acid salt separation membrane material has a thickness of 30 to 60 μm.
[0012] A method for preparing a polyvinylidene fluoride-polyacrylic acid salt separation membrane material comprises the following steps:
[0013] (1) preparing a casting solution: mixing PVDF, PAA and a solvent, and after all components are completely dispersed, the casting solution is allowed to stand for degassing and then used for later use;
[0014] (2) Casting the film casting liquid on the substrate to solidify, then keeping it in a vacuum for a certain period of time, and then immersing the film-coated substrate in a desolidification bath to complete the phase transformation to obtain a film material on the substrate;
[0015] (3) The membrane material is peeled off from the substrate, cleaned, dried, and immersed in a saline-alkali solution to adjust the pH value and ionization degree of the membrane material to obtain a polyvinylidene fluoride-polyacrylate separation membrane material.
[0016] Preferably, the weight average molecular weight Mw of the PVDF in step (1) is 200,000 to 400,000, the weight average molecular weight Mw of PAA is 25,000 to 100,000, and the weight average molecular weight difference is 100,000 to 375,000.
[0017] Preferably, the solvent in step (1) is at least one of N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), trifluoroethanol (TFE), and acetone.
[0018] Preferably, the dispersion in step (1) is stirring or ultrasonic dispersion under heating conditions; wherein the heating temperature is 40°C to 70°C, and the stirring rate is 500rpm to 1500rpm;
[0019] The ultrasonic dispersion time does not exceed 30 minutes;
[0020] Preferably, the stirring and ultrasonic dispersion methods may be repeated or combined for multiple times.
[0021] The standing condition in step (1) is: standing under vacuum for 1 to 2 hours at a temperature of 25-30°C.
[0022] Preferably, the substrate in step (2) is a glass plate, a polytetrafluoroethylene (PTFE) plate, a polypropylene (PP) plate or a stainless steel plate;
[0023] Preferably, a layer of polyethylene terephthalate (PET) film may be selected to cover the surface of the substrate to improve the flatness of the film.
[0024] The coagulation bath described in step (2) is pure water, ethanol or a mixture of the two, the temperature of the coagulation bath is 25-50° C., and the coagulation time is 3-6 minutes.
[0025] Preferably, the concentration of ethanol in the coagulation bath of the mixture does not exceed 30 vol%.
[0026] Preferably, the casting coating method of the casting solution in step (2) is a doctor blade method or a spin coating method;
[0027] The scraper method uses a scraper of 500-1500μm;
[0028] The solidification is solidification in air, the solidification time is 20s to 60s, and the temperature is 25-30°C;
[0029] The vacuum treatment time is 2 minutes to 15 minutes, and the vacuum degree is -0.0999 to -0.093 MPa.
[0030] Preferably, the saline-alkali solution comprises one or more of sodium chloride, lithium chloride, potassium chloride, cesium chloride and their corresponding alkalis, wherein the mass fraction of the solute is 0.01wt% to 10wt%, and the pH value is 8 to 12.
[0031] Preferably, the saline-alkali solution comprises NaCl / NaOH, LiCl / LiOH, KCl / KOH, or CsCl / CsOH.
[0032] Preferably, the cleaning solution in step (3) is ethanol and pure water. The sample is first rinsed with ethanol for 1 to 2 times and then rinsed with pure water for 3 to 5 times to ensure that no solvent remains.
[0033] Preferably, a small amount of saline solution can be introduced during pure water washing to preliminarily ionize PAA.
[0034] The polyvinylidene fluoride-polyacrylic acid salt separation membrane material is used in ethanol / water separation.
[0035] Preferably, the application is the separation of ethanol / water in a low-concentration ethanol aqueous solution under normal temperature and low pressure conditions, the low pressure is no higher than 0.2 MPa, and the concentration of the ethanol aqueous solution is 10.0 vol% to 30.0 vol%.
[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0037] (1) PVDF and PAA are blended to form a separation membrane. The preparation process is simple. The density and thickness of the ethanol retention layer can be adjusted by adjusting the molecular weight, relative ratio and process conditions of the component polymers. The appropriate polymer molecular weight can ensure the mechanical properties of the separation membrane material while controlling the cost. When the PAA ratio is too high, the mechanical strength of the membrane material is insufficient, resulting in almost no selectivity. When the ratio is too low, the selectivity of the membrane material will also be affected, thereby regulating the structure, retention rate and flux of the separation membrane. The dense polyelectrolyte layer PAS in the membrane can effectively retain ethanol molecules, and the amphiphobic component PVDF layer can provide the membrane with strength and a stable channel for water molecules to pass through, while assisting in ethanol retention.
[0038] (2) The separation membrane prepared by the present invention has uniform distribution of functional groups, proper molecular chain entanglement, and good use effect. Unlike the traditional ethanol / water separation method, this new separation membrane does not require the introduction of phase change processes such as heating and cooling, and can be operated at room temperature to reduce energy consumption. At the same time, the operating pressure is low, which reduces the safety risk of the process.
[0039] (3) The separation membrane prepared by the present invention is used for low-pressure separation and filtration of ethanol / water mixture at room temperature, and a certain separation performance is achieved: under an external pressure not higher than 0.2 MPa, for low-concentration ethanol aqueous solution, the separation flux is not less than 0.8 L·m -2 ·h -1 At the same time, the interception rate is stabilized at more than 10%.
[0040] (4) The separation membrane prepared by the present invention has excellent mechanical properties, does not break during the separation process, has more excellent anti-pollution ability, effectively improves the service life and repeatability, and can be used for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the infrared spectrum of pure PVDF film;
[0042] Figure 2This is the infrared spectrum of the PVDF-PAS separation membrane prepared in Inventive Example 5;
[0043] Figure 3 This is a scanning electron microscope image of pure PVDF film formed using the process of the present invention;
[0044] Figure 4 is a scanning electron microscope image of the PVDF-PAS separation membrane prepared in Example 1 of the present invention;
[0045] Figure 5 is a scanning electron microscope image of the PVDF-PAS separation membrane prepared in Example 5 of the present invention;
[0046] Figure 6 This is a mapping diagram of the PVDF-PAS separation membrane prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. For process parameters not specifically noted, conventional techniques may be used. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0048] Embodiment 1:
[0049] A total of 10 g of PVDF powder with a weight average molecular weight Mw of 200,000 and PAA with a weight average molecular weight Mw of 100,000 (PAA 4 g, 40% by mass) were placed in 60 mL of N,N-dimethylacetamide (DMAc) and stirred at 600 rpm at 60 ° C until a clear and uniform solution was obtained. After vacuum degassing for 1 hour, the solution was cast on a polytetrafluoroethylene (PTFE) substrate with a 1000 μm scraper, solidified in air for 30 seconds, and evacuated in a vacuum oven for 5 minutes, and then the PTFE substrate was immersed in a 10 vol% ethanol aqueous solution coagulation bath at 30 ° C for 30 seconds. Thereafter, the separation membrane was peeled off from the substrate, rinsed with anhydrous ethanol twice and deionized water 5 times to remove the residual solvent, and then vacuum dried at 40 ° C and cut to a suitable size. The prepared separation membrane was immersed in a NaCl / NaOH solution with a pH of 10 for 1 hour, and PAA was ionized to form polyacrylate PAS, thereby obtaining a polyvinylidene fluoride-polyacrylate membrane material, which was then further tested for its ability to separate ethanol.
[0050] Embodiment 2:
[0051] A total of 10 g of PVDF powder with a weight average molecular weight Mw of 200,000 and PAA with a weight average molecular weight Mw of 50,000 (PAA 2 g, 20% by mass) were placed in 80 mL of N-methylpyrrolidone (NMP) and stirred at 800 rpm at 70 ° C until a clear and uniform solution was obtained. After vacuum degassing for 2 hours, the casting solution was coated on the PTFE substrate by spin coating, solidified in air for 30 seconds, and evacuated in a vacuum oven for 5 minutes, and then the PTFE substrate was immersed in a 30 ° C deionized water coagulation bath for 60 seconds. Thereafter, the separation membrane was peeled off from the substrate, rinsed with anhydrous ethanol twice and deionized water 5 times to remove the residual solvent, and then it was vacuum dried at 40 ° C and cut to a suitable size. The prepared separation membrane was immersed in a NaCl / NaOH solution with a pH of 10 for 1 hour, and PAA was ionized to form polyacrylate PAS, thereby obtaining a polyvinylidene fluoride-polyacrylate membrane material, which was then further tested for its ability to separate ethanol.
[0052] Embodiment 3:
[0053] A total of 12 g of PVDF powder with a weight average molecular weight Mw of 400,000 and PAA with a weight average molecular weight Mw of 200,000 (PAA 2.4 g, 20% by mass) were placed in 100 mL of DMAc, stirred at 1500 rpm at 60 ° C and assisted by multiple ultrasonic dispersions until a clear and uniform solution was obtained. After vacuum degassing for 2 hours, the solution was cast on a glass substrate with a 750 μm scraper, solidified in air for 60 seconds, and evacuated in a vacuum oven for 6 minutes, and then the glass substrate was immersed in a 20 vol% ethanol aqueous solution coagulation bath at 30 ° C for 60 seconds. Thereafter, the separation membrane was peeled off from the substrate, rinsed twice with anhydrous ethanol and 5 times with deionized water to remove the residual solvent, and then vacuum dried at 40 ° C and cut to a suitable size. The prepared separation membrane was immersed in a NaCl / NaOH solution with a pH of 8 for 1 hour, and PAA was ionized to form polyacrylate PAS, thereby obtaining a polyvinylidene fluoride-polyacrylate membrane material, which was then further tested for its ability to separate ethanol.
[0054] Embodiment 4:
[0055] A total of 10 g of PVDF powder with a weight average molecular weight Mw of 400,000 and PAA with a weight average molecular weight Mw of 50,000 (PAA 4 g, 40% by mass) were placed in 80 mL of NMP and stirred at 1000 rpm at 70 ° C until a clear and uniform solution was obtained. After vacuum degassing for 2 hours, the solution was cast on a glass substrate with a 750 μm scraper, solidified in air for 40 seconds, and evacuated in a vacuum oven for 8 minutes, and then the glass substrate was immersed in a 20 vol% ethanol aqueous solution coagulation bath at 30 ° C for 40 seconds. Thereafter, the separation membrane was peeled off from the substrate, rinsed with anhydrous ethanol twice and deionized water 5 times to remove the residual solvent, and then vacuum dried at 40 ° C and cut to a suitable size. The prepared separation membrane was immersed in a NaCl / NaOH solution with a pH of 10 for 1 hour, and PAA was ionized to form polyacrylate PAS to obtain a polyvinylidene fluoride-polyacrylate membrane material, and then its ability to separate ethanol was further tested.
[0056] Embodiment 5:
[0057] A total of 8 g of PVDF powder with a weight average molecular weight Mw of 400,000 and PAA with a weight average molecular weight Mw of 25,000 (PAA 2.4 g, 30% by mass) were placed in 50 mL of DMF, stirred at 800 rpm at 60 ° C and assisted by multiple ultrasonic dispersions until a clear and uniform solution was obtained. After vacuum degassing for 1 hour, the solution was cast on a PTFE substrate with a 750 μm scraper, solidified in air for 60 seconds, and evacuated in a vacuum oven for 10 minutes, and then the glass substrate was immersed in a 30 ° C deionized water coagulation bath for 60 seconds. Thereafter, the separation membrane was peeled off from the substrate, rinsed with anhydrous ethanol twice and deionized water 5 times to remove the residual solvent, and then vacuum dried at 40 ° C and cut to a suitable size. The prepared separation membrane was immersed in a NaCl / NaOH solution with a pH of 12 for 1 hour, and PAA was ionized to form polyacrylate PAS, thereby obtaining a polyvinylidene fluoride-polyacrylate membrane material, which was then further tested for its ability to separate ethanol.
[0058] Comparative Example 1:
[0059] A total of 8 g of PVDF powder with a weight average molecular weight Mw of 400,000 and PAA with a weight average molecular weight Mw of 25,000 (PAA 4 g, 50% by mass) were placed in 50 mL of DMF, stirred at 1000 rpm at 60 ° C and assisted by multiple ultrasonic dispersions until a clear and uniform solution was obtained. After vacuum degassing for 1 hour, the solution was cast on a PTFE substrate with a 500 μm scraper, solidified in air for 60 seconds, and evacuated in a vacuum oven for 10 minutes, and then the glass substrate was immersed in a 30 ° C deionized water coagulation bath for 60 seconds. Thereafter, the separation membrane was peeled off from the substrate, rinsed with anhydrous ethanol twice and deionized water 5 times to remove the residual solvent, and then vacuum dried at 40 ° C and cut to a suitable size. The prepared separation membrane was immersed in a NaCl / NaOH solution with a pH of 12 for 1 hour, and PAA was ionized to form polyacrylate PAS, thereby obtaining a polyvinylidene fluoride-polyacrylate membrane material, which was then further tested for its ability to separate ethanol.
[0060] Ethanol separation ability test:
[0061] For the separation membranes in Examples 1 to 5 and Comparative Example 1, the ethanol separation efficiency was evaluated and tested according to the normal temperature and low pressure method. An ultrafiltration cup was selected as the pressure filtration equipment, and the gas chromatography method specified in the national standard GB5009.225-2016 was strictly followed to accurately determine the ethanol concentration of the filtered liquid. Further, we calculated the retention rate of the separation membrane using the following formula:
[0062]
[0063] Where R represents the retention rate, C1 is the ethanol concentration in the original solution, and C2 is the ethanol concentration in the filtered solution.
[0064] Regarding the preparation of the test solution, we followed the following steps: first, prepare the infiltration solution by dissolving equimolar amounts of sodium hydroxide and sodium chloride in deionized water and adjusting its pH value to match the pH environment of the filtrate; second, prepare the filtrate, also based on equimolar amounts of hydrochloric acid and sodium chloride, add deionized water to form a salt solution, and then add anhydrous ethanol to ensure that the pH value and ethanol volume fraction of the resulting ethanol salt solution meet the predetermined standards.
[0065] During the test, we used a precision analytical balance to monitor the flow rate of the filtrate. The specific steps are as follows: First, pretreat the separation membrane with a cationic salt solution, and then firmly install it in the ultrafiltration cup; then pour in the ethanol solution to be separated, and the ethanol concentrations of Examples 1 to 5 are 20.0 vol%, 25.0 vol%, 15.0 vol%, 15.0 vol%, and 15.0 vol%, respectively. Use an analytical balance to record the initial mass m1 of the filter device before filtration. Subsequently, under a constant nitrogen pressure, start the filtration process, and periodically take samples from the filtrate for gas chromatography analysis. After the filtration is completed, weigh the mass of the filter device again and record it as m2. Based on the difference between m2 and m1, we can calculate the mass of the filtrate, and convert it into volume based on the concentration-density relationship of the ethanol solution, and then obtain the flux of the filter membrane. The specific calculation formula for the flux is as follows:
[0066]
[0067] Where J is the membrane flux (L·m -2 ·h -1 ), V is the sampling volume (mL), T is the sampling time (h), and A is the membrane effective area (cm 2 ), all test results are summarized in Table 1.
[0068] Table 1: Ethanol separation capacity and filtration flux of PVDF-PAS membrane (25°C)
[0069]
[0070] Based on the above preferred embodiments, it can be concluded that Example 5 successfully prepared an ethanol / water low-pressure separation membrane by virtue of its appropriate functional substance ratio and treatment process. The membrane exhibited good separation performance, specifically a high stable interception rate (16.5%) and a separation flux higher than 0.8 L·m -2 ·h -1 . This performance can be attributed to the good dispersion and reasonable entanglement of the PAS functional layer and the PVDF support layer under this condition. The blended separation membrane of the present invention can not only initially intercept ethanol under normal temperature and low pressure conditions, but also has the ability to be reused, thus reflecting potential economic value. The proportion of PAA in Comparative Example 1 is relatively high, and the insufficient mechanical strength of the membrane material leads to unsatisfactory retention rate and separation flux of the membrane material. Under the same PAA mass proportion conditions, when the molecular weights of PAA and PVDF are close, the corresponding separation effect decreases (such as Examples 2 and 3). In addition, compared with cellulose materials, PVDF has better chemical inertness and mechanical strength, which makes the separation membrane have better anti-pollution ability and mechanical properties, and no damage occurs during the separation process, making it suitable for long-term use.
[0071] Figure 2This is the infrared spectrum of the separation membrane prepared in Example 5 of the present invention, compared with Figure 1 Can clearly find 3200cm -1 There is an obvious carboxyl peak near 1600 cm -1 Nearby, the absorption peak of -COO- group of polyacrylic acid after forming metal salt appears. This proves that the separation chains of PAA and PVDF are fully entangled with each other, which is beneficial to the stability of the casting solution and the coating process as well as the uniformity and stability of the components and functional groups after film formation. Figure 6 It can be seen that the O and F elements are evenly distributed in the separation membrane, which can prove that the polymer components and groups in the separation membrane are evenly distributed. Figure 4 and Figure 5 It can be found that after adding PAA, the surface and internal structure of the membrane material become relatively porous and loose, rather than a completely dense membrane ( Figure 1 ), this porous structure has a larger specific surface area, which is conducive to a more complete contact between the mixed solvent and the membrane material. In addition, when the PAA content is relatively low and the molecular weight difference between PAA and PVDF is larger, it is more conducive to the formation of a relatively dense porous membrane structure ( Figure 5 ), which not only helps to improve the retention rate but also ensures the mechanical properties and repeatability of the membrane.
[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A polyvinylidene fluoride-polyacrylic acid salt separation membrane material, characterized in that: The raw materials include polyvinylidene fluoride PVDF and polyacrylic acid PAA, which are prepared by a phase inversion method; The mass proportion of the PAA is 20% to 40%, and the mass proportion refers to the ratio of the sum of the masses of PAA to PVDF and PAA.
2. The method for preparing the polyvinylidene fluoride-polyacrylic acid salt separation membrane material according to claim 1, characterized in that The steps include: (1) preparing a casting solution: mixing PVDF, PAA and a solvent, and after all components are completely dispersed, the casting solution is allowed to stand for degassing and then used for later use; (2) Casting the film casting liquid on the substrate to solidify, then keeping it in a vacuum for a certain period of time, and then immersing the film-coated substrate in a desolidification bath to complete the phase transformation to obtain a film material on the substrate; (3) The membrane material is peeled off from the substrate, cleaned, dried, and immersed in a saline-alkali solution to obtain a polyvinylidene fluoride-polyacrylate separation membrane material.
3. The method for preparing the polyvinylidene fluoride-polyacrylic acid salt separation membrane material according to claim 2, characterized in that: The weight average molecular weight Mw of the PVDF in step (1) is 200,000 to 400,000, and the weight average molecular weight Mw of PAA is 25,000 to 100,000.
4. The method for preparing the polyvinylidene fluoride-polyacrylic acid salt separation membrane material according to claim 2, characterized in that: The solvent in step (1) is at least one of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide, trifluoroethanol and acetone.
5. The method for preparing the polyvinylidene fluoride-polyacrylic acid salt separation membrane material according to claim 2, characterized in that: The dispersion in step (1) is stirring or ultrasonic dispersion under heating conditions; wherein the heating temperature is 40° C. to 70° C. and the stirring rate is 500 rpm to 1500 rpm; The ultrasonic dispersion time does not exceed 30 minutes; The standing condition in step (1) is: standing under vacuum for 1 to 2 hours at a temperature of 25-30°C.
6. The method for preparing the polyvinylidene fluoride-polyacrylic acid salt separation membrane material according to claim 2, characterized in that: The substrate in step (2) is a polytetrafluoroethylene plate, a glass plate, a polypropylene plate or a stainless steel plate; The coagulation bath described in step (2) is pure water, ethanol or a mixture of the two, the temperature of the coagulation bath is 25-50° C., and the coagulation time is 3-6 minutes.
7. The method for preparing the polyvinylidene fluoride-polyacrylic acid salt separation membrane material according to claim 2, characterized in that: The casting method of the casting solution in step (2) is a scraper method or a spin coating method; The scraper method uses a scraper of 500-1500μm; The solidification is solidification in air, the solidification time is 20s to 60s, and the temperature is 25-30°C; The vacuum treatment time is 2 minutes to 15 minutes, and the vacuum degree is -0.0999 to -0.093 MPa.
8. The method for preparing the polyvinylidene fluoride-polyacrylic acid salt separation membrane material according to claim 2, characterized in that: The saline-alkali solution comprises one or more of sodium chloride, lithium chloride, potassium chloride, cesium chloride and their corresponding alkalis, wherein the mass fraction of the solute is 0.01wt% to 10wt%, and the pH value is 8 to 12.
9. The method for preparing the polyvinylidene fluoride-polyacrylic acid salt separation membrane material according to claim 2, characterized in that: The cleaning solution in step (3) is ethanol and pure water, which is first rinsed with ethanol and then rinsed with pure water.
10. Use of the polyvinylidene fluoride-polyacrylic acid salt separation membrane material according to claim 1 in ethanol / water separation.
Citation Information
Patent Citations
Quaterisation chitosan penetrating and evaporating film, preparation and application thereof
CN101259385A